An Analysis of Students’ Pronunciation Errors at Bilingual Community School - Ni Putu Nia Krisna Dewi; I Nengah Laba; Yohanes Octovianus Lesu Awololon (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study analyzes English pronunciation errors among Year 1 students at a Bilingual Community School in Bali, driven by the need to understand how learners’ first languages influence their ability to articulate English consonants. The aim is to identify recurring errors in voicing, place, and manner of articulation, and to examine the impact of native language interference in a bilingual learning context. The research objectives were achieved by employing a descriptive quantitative research design. Data were collected from 15 bilingual students through pronunciation tests consisting of 70 words, semi-structured interviews to probe linguistic background and pronunciation challenges, and video recordings to observe articulatory movements. Results revealed that, while most students mastered familiar English consonants, persistent errors were noted with sounds absent from their native languages, particularly /θ/, /ð/, /v/, /z/, and /ʃ/. The most frequent errors were characterized by the replacement of unfamiliar English sounds with closer native equivalents, especially in voicing contrasts and tongue placement. These systematic errors were found to be largely attributable to first language interference rather than random mistakes. New insights were provided by focusing on young bilinguals in a dual-language environment, demonstrating that complex interactions between multiple languages shaped distinct pronunciation difficulties. The findings highlighted the necessity of tailored phonetic instruction and focused classroom strategies to address language-specific pronunciation challenges in bilingual settings.